Kandungan Informasi Cum Date Right Issue dan Market Performance - Sukiranto; Sumaryo (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: To examines the effect Cum date right Issue on Abnormal return and Trading stock volume in an emerging economy, Indonesia. Background Problems: Does gap effect cum date right Issue on Abnormal return and Trading stock volume in an emerging economy, Indonesia. Novelty: The Cum date right Issue aspect, one of the important keys to the information content with the stakeholder theory approach, has not been widely discussed on the Indonesia Stock Exchange with solid results Research Methods: Data was collected from published stock price from the Indonesia Stock Exchange. The study sample consists of several companies from mining sector listed on ISX over the period 2016–2020. market performance is measured using abnormal return and trading stock volume indicator with testing for SPSS 25 apliction and method purposive sampling is used for data analysis. Finding/Results: Stakeholders theory in explaining the effect cum date right issue on abnormal return and volume perdagangan saham. Conclusion: These results are key evidence from an emerging country, Indonesia to support the Stakeholders theory arguments. The results provide significant insights for managers at mining sectors.